Precipitation and temperature regulate species diversity, plant coverage and aboveground biomass through opposing mechanisms in large-scale grasslands - Yao, Zhenyu; Xin, Yue; Yang, Liu; Zhao, Liqing; Ali, Arshad (Frontiers in Plant Science, 2022)
Introduction Although the relationships between species diversity and aboveground biomass (AGB) are highly debated in grassland ecosystems, it is not well understood how climatic factors influence AGB directly and indirectly via plant coverage and species diversity in large-scale grasslands along a topographic gradient. In doing so, we hypothesized that climatic factors would regulate plant coverage, species diversity and AGB due to maintaining plant metabolic and ecological processes, but the relationship of plant coverage with AGB would be stronger than species diversity due to covering physical niche space. Methods To test the proposed hypothesis, we collected data for calculations of species richness, evenness, plant coverage and AGB across 123 grassland sites (i.e., the mean of 3 plots in each site) dominated by Leymus chinensis in northern China. We used a structural equation model for linking the direct and indirect effects of topographic slope, mean annual precipitation and temperature on AGB via plant coverage, species richness, and evenness through multiple complex pathways. Results We found that plant coverage increased AGB, but species evenness declined AGB better than species richness. Topographic slope influenced AGB directly but not indirectly via plant coverage and species diversity, whereas temperature and precipitation increased with increasing topographic slope. Regarding opposing mechanisms, on the one hand, precipitation increased AGB directly and indirectly via plant coverage as compared to species richness and evenness. On the other hand, temperature declined AGB indirectly via plant coverage but increased via species evenness as compared to species richness, whereas the direct effect was negligible. Discussion Our results show that niche complementarity and selection effects are jointly regulating AGB, but these processes are dependent on climatic factors. Plant coverage promoted the coexistence of species but depended greatly on precipitation and temperature. Our results highlight that precipitation and temperature are two key climatic drivers of species richness, evenness, plant coverage and AGB through complex direct and indirect pathways. Our study suggests that grasslands are sensitive to climate change, i.e., a decline in water availability and an increase in atmospheric heat. We argue that temperature and precipitation should be considered in grassland management for higher productivity in the context of both plant coverage and species diversity which underpin animals and human well-being.